Preparation method of PET-PEN copolyester monomer
By mixing 2,6-dialkylnaphthalene and oxidizing xylene in the presence of an oxidation catalyst and solvent, the problems of complex preparation process and high energy consumption of PET_PEN copolyester monomer are solved, and the product is improved Purity and performance achieve a balance between cost and performance.
Patent Information
- Application Number
- CN202310775642.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
The existing PET_PEN copolyester monomer preparation process is complex and the oxidation catalyst energy consumption is high, making it difficult to simultaneously increase the purity of 2,6-NDCA and PTA monomers, limiting the performance and cost of polyester products.
In the presence of an oxidation catalyst and the first solvent, mix 2,6-dialkylnaphthalene and contact p-xylene with oxygen for oxidation reaction, and purify it to reduce the energy consumption of the oxidation catalyst and increase the purity of the PET_PEN copolyester monomer .
The process flow is simplified, the energy consumption of the oxidation catalyst is reduced, the purity of the PET_PEN copolyester monomer is significantly improved and the impurity content is reduced, achieving the dual advantages of economy and performance.
Smart Images

Figure BDA0004309266270000171 
Figure BDA0004309266270000181 
Figure BDA0004309266270000191
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of compound preparation, and in particular to a method for preparing PET_PEN copolyester monomers. Background Art
[0002] Purified terephthalic acid (PTA), as an important polyester monomer, is mainly used to produce polyester products such as polyethylene terephthalate (PET), polypropylene terephthalate (PTT) and polybutylene terephthalate (PBT). The PTA production process is mainly divided into two categories: one is to first oxidize paraxylene (PX) with air and crystallize it to obtain crude terephthalic acid (CTA), and then hydrogenate CTA to obtain high-purity PTA, which is called the two-step method. This method accounts for more than 80% of PTA production capacity; the other is to only undergo precise oxidation and crystallization separation of PX to obtain medium-purity PTA (MPTA or EPTA) for polymerization, which is called the one-step method.
[0003] 2,6-Naphthalene dicarboxylic acid (2,6-NDCA) is an important monomer for the preparation of various polyesters, polyurethane materials, and liquid crystal polymers (LCP). In particular, polyethylene naphthalate (PEN) prepared by the polymerization of 2,6-NDCA and ethylene glycol (EG) has broad application prospects in packaging containers (especially beer bottles), films, and industrial-grade fibers. The mainstream industrial-grade production process of 2,6-NDCA mainly includes the preparation of crude 2,6-NDCA and its purification. The preparation of crude 2,6-NDCA by air oxidation of 2,6-dialkylnaphthalene (mainly 2,6-dimethylnaphthalene, 2,6-diisopropylnaphthalene, and 2,6-diethylnaphthalene) is the main method for the industrial production of crude 2,6-NDCA. The purification methods of crude 2,6-NDCA mainly used in industrial production include esterification and hydrogenation to purify crude 2,6-NDCA. The advantage of the esterification method is the high purity of the product, but the disadvantage is the complex process, high material and energy consumption, and high product production cost; the advantage of the hydrogenation method is the simple process route, but the disadvantage is the high requirements for equipment materials, and catalyst powder will be brought into the product, thereby affecting subsequent polymerization.
[0004] Due to the high symmetry of the molecular structure of 2,6-NDCA, PEN has the characteristics of a linear polymer. It is a high-performance polyester material with high strength, good rigidity and excellent thermal processing performance. Compared with PET, PEN has better heat resistance, barrier properties, mechanical properties, chemical resistance, UV resistance and other properties. However, compared with PET, the price of PEN is very high (the price of PEN is usually 5-10 times that of PET), which greatly limits its application and development. Therefore, in the polyester industry, 2,6-NDCA and PTA are often prepared in a certain proportion to form PET_PEN copolyester monomers, and then polymerized and polycondensed with ethylene glycol (EG) to obtain PET_PEN copolyesters. This can not only obtain polyester products with superior performance, but also greatly reduce the production cost of polyester products.
[0005] CN115722157A discloses a reaction system and method for preparing 2,6-naphthalenedicarboxylic acid by oxidation of 2,6-diisopropylnaphthalene, wherein the oxidation raw material is 2,6-diisopropylnaphthalene, and p-xylene is not included. Only an oxidation process is involved, and crude 2,6-NDCA is finally obtained, and PET_PEN copolyester monomer cannot be directly obtained.
[0006] CN112521271A discloses a method for hydrogenating and refining crude 2,6-naphthalene dicarboxylic acid, which does not involve oxidation reaction, and the hydrogenating and refining raw materials do not include crude terephthalic acid. The final product is 2,6-NDCA, and PET_PEN copolyester monomer cannot be directly obtained. Summary of the invention
[0007] 2,6-Naphthalene dicarboxylic acid (2,6-NDCA) is a monomer used to prepare polyethylene naphthalate (PEN), and purified terephthalic acid (PTA) is a monomer used to prepare polyethylene terephthalate (PET). PET has the advantages of low cost and excellent appearance performance, but its heat resistance and barrier properties cannot meet the requirements of certain fields. PEN has good heat resistance and barrier properties, but it is expensive. At present, economical PET and good-performance PEN are blended to form copolyesters to prepare products with good economy and performance. There are two main methods for forming copolyesters. The first is to directly blend PET and PEN, and the second is to blend 2,6-NDCA monomers, PTA monomers and ethylene glycol to obtain PET_PEN copolyesters. The inventors studied the second method: In the second method, it is necessary to It is necessary to prepare 2,6-NDCA monomer and PTA monomer separately, but compared with the preparation of PTA monomer, the preparation of 2,6-NDCA monomer is more difficult, and both need to go through two-step processes to prepare 2,6-NDCA monomer and PTA monomer separately. Not only is the process cumbersome but also requires high oxidation catalyst energy consumption. Based on this, the inventor first proposed to use a one-step process to prepare a material containing 2,6-NDCA monomer and PTA monomer (i.e., PET_PEN copolyester monomer), and in the study the inventor unexpectedly found that the raw material 2,6-dialkylnaphthalene for preparing 2,6-NDCA and the raw material p-xylene for preparing PTA monomer are mixed to prepare a material containing 2,6-NDCA monomer and PTA monomer, which can also improve the purity of PET_PEN copolyester monomer compared with preparing 2,6-NDCA monomer and PTA monomer separately from the two.
[0008] Based on the above findings, the present invention provides for the first time a method for preparing a PET_PEN copolyester monomer, the method comprising: in the presence of an oxidation catalyst and a first solvent, a raw material containing 2,6-dialkylnaphthalene and p-xylene is contacted with an oxygen-containing gas for oxidation reaction, followed by refining.
[0009] Through the above technical scheme, the mixed oxidation reaction of terephthalic acid and 2,6-dialkylnaphthalene followed by refining has a significant improvement effect compared with the oxidation reaction of the two alone and the refining afterwards, and can improve the purity of terephthalic acid / 2,6-naphthalene dicarboxylic acid products and reduce the impurity content. DETAILED DESCRIPTION
[0010] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0011] In the present invention, "PET_PEN copolyester monomer" refers to a mixture of 2,6-NDCA monomer and PTA monomer.
[0012] The present invention proposes for the first time a method for preparing a PET_PEN copolyester monomer, the method comprising: in the presence of an oxidation catalyst and a first solvent, a raw material containing 2,6-dialkylnaphthalene and p-xylene is contacted with an oxygen-containing gas for oxidation reaction, and then refined.
[0013] In the present invention, 2,6-dialkylnaphthalene and p-xylene are mixed to prepare PET_PEN copolyester monomer, which can not only reduce the energy consumption of the oxidation catalyst but also improve the purity of the PET_PEN copolyester monomer.
[0014] According to the present invention, in some preferred embodiments, in the raw material, the weight ratio of 2,6-dialkylnaphthalene to p-xylene is 0.020-0.111:1, preferably 0.042-0.064:1. By adopting the above embodiment, the prepared PET_PEN copolyester monomer has higher purity and lower energy consumption of the oxidation catalyst.
[0015] According to the present invention, the amount of the oxidation catalyst can be selected to promote the oxidation reaction. In some embodiments, the weight ratio of the oxidation catalyst to the first solvent is 0.01-0.035:1, for example, 0.01:1, 0.168:1, 0.02:1, 0.03:1 or 0.035:1, and a range consisting of any two of the above ratios.
[0016] According to the present invention, the amount of the first solvent can be selected to promote the oxidation reaction. In some embodiments, the weight ratio of the first solvent to the raw material is 1.5-9:1, for example, 1.5:1, 2:1, 3.5:1, 4:1, 6:1, 7:1, 8:1, or 9:1, and a range consisting of any two of the above ratios, preferably 4-9:1.
[0017] According to the present invention, 2,6-dialkylnaphthalene is a raw material for preparing 2,6-NDCA monomer. As long as the corresponding 2,6-NDCA monomer can be obtained, the specific selection of 2,6-dialkylnaphthalene is not particularly limited. In some embodiments, the 2,6-dialkylnaphthalene is selected from at least one of 2,6-dimethylnaphthalene, 2,6-diisopropylnaphthalene and 2,6-diethylnaphthalene.
[0018] According to the present invention, in some preferred embodiments, the 2,6-dialkylnaphthalene is 2,6-diisopropylnaphthalene. By adopting the above preferred embodiments, a PET_PEN copolyester monomer with high purity and low impurity content can be obtained.
[0019] According to the present invention, the first solvent capable of promoting the oxidation reaction may be selected as required. In some embodiments, the first solvent includes at least one of carboxylic acid substances and optionally water.
[0020] The optional water mentioned in the present invention means that water may or may not be added to the first solvent. In some preferred embodiments, the water content in the first solvent is ≤8 wt %.
[0021] According to the present invention, as long as the purpose of the present invention can be achieved, the carboxylic acid substance in the first solvent is not particularly limited. In some preferred embodiments, the carboxylic acid substance is selected from saturated fatty acids, preferably C2-C6 saturated fatty acids, such as at least one of acetic acid, propionic acid, butyric acid, valeric acid and caproic acid, preferably acetic acid. By adopting the above embodiment and the above preferred embodiment, a PET_PEN copolyester monomer with high purity and low impurity content can be obtained.
[0022] According to the present invention, "oxygen-containing gas" refers to a gas that can provide oxygen, which can be oxygen alone or a mixed gas of oxygen and other gases. In some embodiments, the oxygen-containing gas is selected from oxygen and / or air; wherein, for economic considerations, air is used to provide oxygen in the present invention, but the present invention is not limited to this.
[0023] According to the present invention, there is no particular limitation on the oxidation catalyst as long as it can enable the oxidation reaction to proceed well. In some embodiments, the active components of the oxidation catalyst include manganese, bromine, cobalt and optionally potassium.
[0024] In the present invention, the manganese oxide element, bromine element, cobalt element and potassium element may exist in the oxidation catalyst in an active form, such as in the form of ions or other forms. In some preferred embodiments, the manganese element, bromine element and cobalt element each come from a salt of the corresponding element; that is, the manganese element is provided by a manganese salt, the bromine element is provided by a bromine salt, and the cobalt element is provided by a cobalt salt.
[0025] According to the present invention, preferably, the manganese element is provided by manganese carboxylate, preferably by C1-C5 saturated fatty acid manganese, such as manganese formate, manganese acetate or manganese propionate; commercially available manganese carboxylates often exist in the form of hydrates, and manganese acetate tetrahydrate is used as an example in the present invention, but the present invention is not limited thereto.
[0026] According to the present invention, preferably, the potassium element is provided by potassium carboxylate, preferably by saturated fatty acid potassium, further preferably by C1-C5 saturated fatty acid potassium, for example, at least one of potassium formate, potassium acetate and potassium propionate. In the present invention, potassium acetate is used as an example, but the present invention is not limited thereto.
[0027] According to the present invention, preferably, the cobalt element is provided by a cobalt carboxylate, preferably by a saturated fatty acid cobalt, and further preferably by a C1-C5 saturated fatty acid cobalt, for example, at least one of cobalt formate, cobalt acetate and cobalt propionate; commercially available cobalt carboxylates often exist in the form of hydrates, and cobalt acetate tetrahydrate is used as an example in the present invention, but the present invention is not limited thereto.
[0028] According to the present invention, preferably, the bromine element is selected from bromides, preferably at least one of potassium bromide, tetrabromoethane and ammonium bromide. Potassium bromide is used as an example in the present invention, but the present invention is not limited thereto.
[0029] According to the present invention, as long as the purpose of the present invention can be achieved, the amounts of the various components in the oxidation catalyst are not particularly limited. In some preferred embodiments, the molar ratio of the cobalt salt to the manganese salt is 1.5-4.5:1, preferably 2.0-3.5:1.
[0030] According to the present invention, in some preferred embodiments, the molar ratio of the sum of the cobalt salt and the manganese salt to the bromide is 0.7-1.5:1, preferably 0.85-1.25:1.
[0031] According to the present invention, in some preferred embodiments, the weight ratio of potassium salt to oxidation catalyst is 0.1-0.85:1, preferably 0.3-0.65:1.
[0032] According to the present invention, during the oxidation reaction, the oxidation catalyst and the first solvent may be fed separately or as a mixed solution. In the present invention, the oxidation catalyst and the first solvent are mixed and then fed for the oxidation reaction.
[0033] According to the present invention, in some embodiments, the oxidation reaction is a continuous oxidation reaction; preferably, part of the raw material is first added as a raw material mother liquor, and a mixture of part of the oxidation catalyst and part of the first solvent is fed in advance as a solution mother liquor containing the oxidation catalyst to carry out a pre-oxidation reaction under the conditions of the oxidation reaction, and then the raw material and the mixture of the oxidation catalyst and the first solvent are continuously fed at a certain flow rate to continue the continuous oxidation reaction; wherein, the flow rates of the raw material and the mixture of the oxidation catalyst and the first solvent are not particularly limited; for example, the flow rate of the raw material: raw material mother liquor = (0.5-1.5) g / min: 100g, specifically such as 0.5g / min: 100g, 0.8g / min: 100g, 1g / min: 100g, 1.2g / min: 100g or 1.5g / min: 100g; a mixed solution of the oxidation catalyst and the first solvent: a mother liquor containing the oxidation catalyst = (0.5-1.5)g / min: 100g, specifically such as 0.5g / min: 100g, 0.8g / min: 100g, 1g / min: 100g, 1.2g / min: 100g or 1.5g / min: 100g.
[0034] According to the present invention, in some embodiments, the molar ratio of oxygen in the oxygen-containing gas to the raw material is 2.5-9:1, for example, 2.5:1, 2.8:1, 3.0:1, 3.5:1, 4.5:1, 5.0:1, 6.0:1, 7:1, 8:1 or 9:1, and a range consisting of any two of the above values, preferably 2.8-4.0:1.
[0035] According to the present invention, in some preferred embodiments, based on the advance feeding of 1000g of the raw material and the continuous feeding of the raw material at 10g / min, the flow rate of the oxygen-containing gas at the standard state is 20.0-88.0L / min, for example, 20.0L / min, 25.0L / min, 30.0L / min, 40.0L / min, 50.0L / min, 60.0L / min, 70.0L / min or 88.0L / min, and the range composed of any two of the above values, preferably 20.0-60.0L / min.
[0036] According to the present invention, in some preferred embodiments, the oxygen content in the oxygen-containing gas is 18-25 vol%, and the partial pressure of the oxygen-containing gas is 0.3-0.8 MPa.
[0037] According to the present invention, it is understood that in order to increase the speed of the oxidation reaction, it is generally carried out under stirring conditions, for example, the stirring speed is 50-100 rpm.
[0038] According to the present invention, the conditions for the oxidation reaction, specifically the reaction temperature, reaction pressure, reaction time and the like, are not limited as long as the oxidation reaction can proceed satisfactorily.
[0039] According to the present invention, in some embodiments, the conditions of the oxidation reaction include: the reaction temperature is 160-220°C, preferably 170-200°C.
[0040] According to the present invention, in some embodiments, the conditions of the oxidation reaction include: the reaction pressure is 1.8-4.0 MPa, preferably 2.0-3.5 MPa.
[0041] According to the present invention, during the oxidation reaction, when the reaction temperature exceeds the boiling point of the solvent, a pressure-resistant reactor device can be used for the reaction, and the system itself may generate pressure. At this time, the pressure in the reactor can be adjusted by the back pressure valve of the reactor device so that the reaction pressure is 1.8-4.0MPa, preferably in the range of 2.0-3.5MPa, and the partial pressure of the oxygen-containing gas is 0.3-0.8MPa. This embodiment makes the pressure of the reactor device higher than the sum of the saturated vapor pressure of the solvent and the partial pressure of the oxygen-containing gas, ensuring that the reactants are always in a liquid phase;
[0042] According to the present invention, in some embodiments, based on the advance feeding of 1000 g of the raw material and the continuous feeding of the raw material at 10 g / min, the partial pressure of the oxidant is 0.3-0.8 MPa.
[0043] According to the present invention, 2,6-dialkylnaphthalene and para-xylene are usually present in solid form. In order to realize continuous oxidation reaction, the raw material containing 2,6-dialkylnaphthalene and para-xylene can be heated to make the raw material in liquid phase. That is, in some embodiments, the conditions of the oxidation reaction include: the raw material is a liquid raw material, and the residence time of the liquid raw material in the oxidation reaction is 0.5-2.0h, preferably 0.9-1.8h.
[0044] According to the present invention, the reaction material obtained after the oxidation reaction is generally a material containing crude 2,6-naphthalene dicarboxylic acid / terephthalic acid, and the crude 2,6-naphthalene dicarboxylic acid / terephthalic acid needs to be refined. In some embodiments, the refining process includes: hydrogen is contacted with a slurry containing crude 2,6-naphthalene dicarboxylic acid / terephthalic acid obtained by the oxidation reaction in the presence of a hydrogenation catalyst and a second solvent for hydrogenation refining.
[0045] According to the present invention, the oxidation reaction will obtain a material containing crude 2,6-naphthalene dicarboxylic acid / terephthalic acid, and the material contains a first solvent and optionally impurities. In some embodiments, the material obtained by the oxidation reaction is subjected to solid-liquid separation, optional washing separation, water solvent replacement, and drying to obtain crude 2,6-naphthalene dicarboxylic acid / terephthalic acid; wherein, the method for solid-liquid separation can be a conventional method in the art for separation, such as filter pressing under a certain pressure difference to obtain a solid filter cake; "optionally washing separation" means that washing separation can be performed or not, preferably washing separation, and the washing separation method can be: washing with the first solvent and solid-liquid separation to obtain a filter cake; the filter cake obtained after solid-liquid separation and optional washing separation still contains part of the first solvent, and water solvent replacement refers to using water to replace all or most of the first solvent in the filter cake, that is, washing the filter cake with water before separation, wherein the number of washing separation and water solvent replacement can be 1 time or at least two times as needed; the drying method can be a conventional method in the art, such as drying at 110-140°C for 12-48h.
[0046] According to the present invention, as long as the purpose of the present invention can be achieved, when performing hydrogenation refining, the type of the hydrogenation catalyst is not particularly limited. In some embodiments, the hydrogenation catalyst is selected from a supported precious metal catalyst. By adopting the above embodiment, a PET_PEN copolyester monomer with high purity and low impurity content can be obtained.
[0047] According to the present invention, in some embodiments, the particle size of the supported noble metal catalyst is 5-8 mesh.
[0048] According to the present invention, "supported precious metal catalyst" refers to precious metal as an active component supported on a corresponding carrier. Considering the effect and economy of hydrogenation refining, in some embodiments, the content of precious metal in the supported precious metal catalyst is 0.1-0.8wt%, preferably 0.35-0.65wt%.
[0049] According to the present invention, as long as the purpose of the present invention can be achieved, the type of precious metal is not particularly limited. In some embodiments, in the supported precious metal catalyst, the precious metal is selected from one or more of palladium, ruthenium and tin, preferably palladium and tin.
[0050] According to the present invention, in some preferred embodiments, the weight ratio of palladium to tin is 1-9:1, preferably 1.86-5.67:1.
[0051] According to the present invention, "slurry containing crude 2,6-naphthalene dicarboxylic acid / terephthalic acid obtained by oxidation reaction" refers to a slurry formed by mixing crude 2,6-naphthalene dicarboxylic acid / terephthalic acid obtained by oxidation reaction with a solvent. As long as the purpose of the present invention can be achieved, the solvent in the slurry is not particularly limited. In some embodiments, the solvent in the slurry includes a mixture of carboxylic acid substances and water. By adopting the above-mentioned embodiment, a PET_PEN copolyester monomer with high purity and low impurity content can be obtained.
[0052] According to the present invention, in some preferred embodiments, the weight ratio of the carboxylic acid substance to water is 0.01-0.1:1, for example, 0.01:1, 0.015:1, 0.016:1, 0.021:1, 0.03:1, 0.05:1, 0.06:1, 0.08:1, 0.9:1 or 0.1:1, and a range consisting of any two of the above ratios, preferably 0.15-0.08:1. By adopting the above embodiment, a PET_PEN copolyester monomer with high purity and low impurity content can be obtained.
[0053] According to the present invention, in some preferred embodiments, the carboxylic acid substance is selected from one or more of formic acid, acetic acid and propionic acid, preferably acetic acid. By adopting the above embodiment, a PET_PEN copolyester monomer with high purity and low impurity content can be obtained.
[0054] According to the present invention, the amount of solvent used to form the slurry with crude 2,6-naphthalene dicarboxylic acid / terephthalic acid is sufficient as long as the crude 2,6-naphthalene dicarboxylic acid / terephthalic acid can be better hydrofined. In some embodiments, the weight ratio of the solvent to the crude 2,6-naphthalene dicarboxylic acid / terephthalic acid in the slurry is 15-40:1, preferably 18-30:1. The above-mentioned embodiment can make the hydrofining well performed and obtain high-purity PET_PEN copolyester monomer with low impurity content.
[0055] According to the present invention, in some embodiments, the second solvent comprises water.
[0056] According to the present invention, in some embodiments, the mass ratio of the weight of the second solvent to the mass of the hydrogenation catalyst is 0.1-1:1, preferably 0.2-0.5:1.
[0057] According to the present invention, in some embodiments, the weight space velocity LHSV of the crude 2,6-naphthalene dicarboxylic acid / terephthalic acid slurry relative to the fixed bed of palladium carbon catalyst is n 0.25-6h -1 , preferably 1-5h -1According to the present invention, during the refining, the conditions for hydrofining, specifically the liquid hourly weight space velocity of the slurry, the reaction temperature, the hydrogen partial pressure, etc., are sufficient as long as the crude 2,6-naphthalene dicarboxylic acid / terephthalic acid can be purified and refined well.
[0058] According to the present invention, in some embodiments, the hydrofining conditions include: relative to the hydrogenation catalyst, the liquid hourly weight space velocity LHSV of the slurry n 0.25-10h -1 , preferably 0.5-8h -1 .
[0059] According to the present invention, in some embodiments, the conditions for the hydrofining include: the reaction temperature is 250-310°C, preferably 270-290°C.
[0060] According to the present invention, in some embodiments, the hydrogen partial pressure is 0.05-3.0 MPa, preferably 0.5-1.5 MPa.
[0061] According to the present invention, the material obtained after hydrogenation refining also contains a solvent, and the PET_PEN copolyester monomer in the material obtained after hydrogenation refining can be separated by conventional methods in the art. In some embodiments, the preparation method described in the present invention also includes: solid-liquid separation, washing, and drying of solid-phase materials after hydrogenation refining; wherein the solid-liquid separation method can be a conventional method in the art, such as using positive / negative pressure filtration or centrifugal equipment to perform solid-liquid separation to obtain a solid-phase material; water can be used for washing in a high-temperature and high-pressure washing tank, for example, water and solid-phase materials are mixed and added to a high-temperature and high-pressure washing tank for mixed washing at 170-195°C; drying of the solid-phase material refers to drying the solid-phase material obtained after washing.
[0062] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0063] Purity analysis method of PTA / 2,6-NDCA in the product: quantitative determination by Agilent 1260 high performance liquid chromatography. Qualitative analysis: using standard PTA / 2,6-NDCA sample for liquid chromatography test, spectrum 1 was obtained. Under the same conditions, the dried product was subjected to liquid chromatography test, and spectrum 2 was obtained. Comparative analysis of spectrum 1 and spectrum 2 showed that the retention time and peak shape were completely consistent with the standard, proving that the main product was PTA / 2,6-NDCA.
[0064] Quantitative analysis (purity determination): Determine the peak area of PTA / 2,6-NDCA based on a standard sample of known purity, then determine the peak area of the sample PTA / 2,6-NDCA, and compare the two to obtain the purity of the sample PTA / 2,6-NDCA.
[0065] Analysis of impurity content in the product: quantitative determination by Agilent 1260 high performance liquid chromatography. According to the analysis results of literature and mass spectrometry, key impurities (p-carboxybenzaldehyde and p-methylbenzoic acid will have a significant impact on the color and polymerization of the final purified product PTA, 2-methyl-6-naphthoic acid and 2-acetyl-6-naphthoic acid will have a significant impact on the color and polymerization of the final purified product 2,6-NDCA, and changes of tens or tens of ppm of the above impurities will have a very large impact on the polymer) and their peak times. According to the key impurity standard sample with known purity, the peak area of the key impurity is measured, and then the peak area of the key impurity of the sample is measured. By comparing the two, the key impurity content in the sample can be obtained.
[0066] The present invention will be described in detail below through examples. In the following examples and comparative examples: 4-CBA represents p-carboxybenzaldehyde, PT acid represents p-toluic acid, the overhydrogenated product represents 2,6-dicarboxy-1,2,3,4-tetrahydronaphthalene, 2-FNA represents 2-methyl-6-naphthoic acid, and 2-ANA represents 2-acetyl-6-naphthoic acid.
[0067] Example 1
[0068] Prepare a solution containing a catalyst: based on a total of 100 g, 2.22 g of cobalt acetate tetrahydrate, 4.04 g of manganese acetate tetrahydrate, 3.64 g of potassium bromide, 4.50 g of potassium acetate, and 85.60 g of acetic acid. Stir the mixture thoroughly and preheat to 150° C. to make it a solution.
[0069] Preparation of oxidation raw materials: Based on a total amount of 100 g, 5 g of 2,6-diisopropylnaphthalene (2,6-DIPN) and 95 g of p-xylene (PX) were fully mixed and preheated to 150° C. to form a uniform liquid phase;
[0070] 1015.00 g of the above-mentioned oxidation raw material and 8176.92 g of the above-mentioned catalyst-containing solution were pre-added to the oxidation reactor, the stirring paddle was turned on and its speed was set to 60 rpm, and when the temperature was raised to 160°C, air was introduced into the oxidation reactor at a flow rate of 50.0 L / min (standard state) and the air partial pressure was controlled at 0.5 MPa. The back pressure valve behind the tail gas outlet was adjusted to control the pressure in the reactor to 4.0 MPa, and the tail gas generated by the reaction was continuously discharged through the tail gas outlet. The reaction temperature was controlled at 19 0°C, react for 30 minutes; add the oxidation raw material and the catalyst-containing solution to the bottom of the oxidation reactor through the raw material inlet and the catalyst inlet at a rate of 10.15 g / min and 81.77 g / min, respectively; after reacting for 30 minutes, continuously discharge the crude terephthalic acid (TA) / 2,6-naphthalenedicarboxylic acid (2,6-NDCA) slurry outlet at a rate of 91.92 g / min (crude TA / 2,6-NDCA oxidation slurry), and collect the crude TA / 2,6-NDCA oxidation slurry;
[0071] 100 g of the crude TA / 2,6-NDCA oxidation slurry was sequentially subjected to the following treatments: direct pressure filtration at a pressure difference of 0.5 MPa for 10 min to obtain filter cake A1; 50 g of acetic acid was added to filter cake A1 and mixed thoroughly, and then pressure filtration was performed at a pressure difference of 0.2 MPa for 5 min to obtain filter cake A2; 25 g of acetic acid was added to filter cake A2, and then pressure filtration was performed at a pressure difference of 0.2 MPa for 5 min to obtain filter cake A3; 50 g of pure water was added to filter cake A3, and then pressure filtration was performed at a pressure difference of 0.2 MPa for 5 min to obtain filter cake A4; 25 g of pure water was added to filter cake A4, and then pressure filtration was performed at a pressure difference of 0.2 MPa for 5 min to obtain filter cake A5; filter cake A5 was placed in an oven at 120° C. for 24 h to dry, and filter cake A6 was obtained;
[0072] Prepare a crude TA / 2,6-NDCA slurry (based on 100 parts by weight, 2 parts of acetic acid, 4 parts of filter cake A6, and 94 parts of pure water), stir and mix thoroughly, and preheat to 280° C. to make it a uniform solution;
[0073] 50.0 g of pure water was added to a fixed bed hydrogenation reactor, and then 179.29 g of a palladium-tin-carbon catalyst with a palladium content of 0.33 wt% and a tin content of 0.15 wt% and a particle size of 5-8 mesh was added, and then the temperature was raised to 280° C., and hydrogen was introduced. The hydrogen partial pressure was controlled at 0.60 MPa. The crude TA / 2,6-NDCA slurry was added to the fixed bed hydrogenation reactor at a rate of 7.41 g / min to start the reaction. After the reaction was carried out for 5 hours, the hydrogenation purification material was collected, and the hydrogenation purification material 2 was taken. 000g, positive pressure filtration equipment is used for solid-liquid separation to obtain a solid phase material (containing about 10wt% water, 80.0g hydrogenated purified PTA / 2,6-NDCA), which is then added to a high-temperature and high-pressure washing tank, and then 160g of pure water is added, stirring is started (200rpm), and the temperature is raised to 185°C after sealing and pressure testing. The solid phase material is obtained after filtration and then dried, and finally PTA / 2,6-NDCA sample A7 (i.e., PET_PEN copolyester monomer) is obtained for sample analysis. The analysis results are shown in Table 1.
[0074] Example 2
[0075] The method of Example 1 was followed, except that the air partial pressure was controlled at 0.8 MPa to introduce air into the oxidation reactor. Finally, the PTA / 2,6-NDCA sample E7 (i.e., PET_PEN copolyester monomer) was obtained and sent for analysis. The analysis results are shown in Table 1.
[0076] Example 3
[0077] The method of Example 1 was followed, except that the palladium-tin-carbon catalyst had a palladium content of 0.38 wt% and a tin content of 0.1 wt% and a particle size of 5-8 mesh. Finally, the PTA / 2,6-NDCA sample F7 (i.e., PET_PEN copolyester monomer) was obtained and sent for analysis. The analysis results are shown in Table 1.
[0078] Example 4
[0079] The method of Example 1 was followed, except that a crude TA / 2,6-NDCA slurry (based on 100 parts by weight, 2 parts of acetic acid, 3.5 parts of filter cake A6, and 94.5 parts of pure water) was prepared, fully stirred and mixed, and then preheated to 280°C to make it a uniform solution state. Finally, a PTA / 2,6-NDCA sample G7 (i.e., PET_PEN copolyester monomer) was obtained and sent for analysis. The analysis results are shown in Table 1.
[0080] Example 5
[0081] The method of Example 2 was followed, except that a crude TA / 2,6-NDCA slurry (100 parts, 1.5 parts acetic acid, 4 parts filter cake A6, 94.5 parts pure water) was prepared, fully stirred and mixed, and then preheated to 280°C to make it a uniform solution state. Finally, a PTA / 2,6-NDCA sample H7 (i.e., PET_PEN copolyester monomer) was obtained and sent for analysis. The analysis results are shown in Table 1.
[0082] Example 6
[0083] The method of Example 1 was followed, except that: the oxidation raw material was prepared: based on a total amount of 100 g, 1.5 g of 2,6-diisopropylnaphthalene (2,6-DIPN) and 98.5 g of p-xylene (PX) were fully mixed and preheated to 150° C. to make them into a uniform liquid phase. Finally, the PTA / 2,6-NDCA sample J7 (i.e., PET_PEN copolyester monomer) was obtained and sent for analysis. The analysis results are shown in Table 1.
[0084] Example 7
[0085] The method of Example 3 was followed, except that: the oxidation raw material was prepared: based on a total amount of 100 g, 12 g of 2,6-diisopropylnaphthalene (2,6-DIPN) and 88 g of p-xylene (PX) were fully mixed and preheated to 150° C. to make them into a uniform liquid phase. Finally, the PTA / 2,6-NDCA sample K7 (i.e., PET_PEN copolyester monomer) was obtained and sent for analysis. The analysis results are shown in Table 1.
[0086] Comparative Example 1
[0087] Prepare a catalyst-containing solution 1: based on a total of 100 g, 2.22 g of cobalt acetate tetrahydrate, 4.04 g of manganese acetate tetrahydrate, 3.64 g of potassium bromide, 4.50 g of potassium acetate, and 85.60 g of acetic acid;
[0088] Prepare catalyst-containing solution 2: based on a total of 100 g, 4.50 g of cobalt acetate tetrahydrate, 3.38 g of manganese acetate tetrahydrate, 3.55 g of potassium bromide, 3.73 g of potassium acetate, and 84.83 g of acetic acid;
[0089] The catalyst-containing solution 1 and the catalyst-containing solution 2 are respectively fully stirred and preheated to 150° C. to make them into a solution state;
[0090] Preparation of oxidation raw materials 1: Preheat a certain amount of PX to 100°C;
[0091] Preparation of oxidation raw material 2: preheat a certain amount of 2,6-DMN to 150°C to melt it into liquid;
[0092] 1015.00g of the above-mentioned oxidation raw material 1 and 8176.92g of the above-mentioned catalyst-containing solution 1 were pre-added to the oxidation reactor, the stirring paddle was turned on and its speed was set to 60rpm, when the temperature was raised to 160°C, air was introduced into the oxidation reactor at a flow rate of 50.0L / min (standard state), and the air partial pressure was controlled at 0.5MPa, the back pressure valve behind the tail gas outlet was adjusted to control the pressure in the reactor to 4.0MPa, and the tail gas generated by the reaction was continuously discharged through the tail gas outlet, the reaction temperature was controlled at 190°C, after 30 minutes of reaction, the oxidation raw material 1 and the catalyst-containing solution 1 were added to the bottom position of the oxidation reactor through the raw material inlet and the catalyst inlet at a rate of 10.15g / min and 81.77g / min, respectively, after 30 minutes of reaction, the crude TA slurry outlet was continuously discharged at a rate of 91.92g / min (crude TA oxidation slurry), and the crude TA oxidation slurry was collected;
[0093] 100 g of the crude TA oxidation slurry was subjected to the following treatments in sequence: direct pressure filtration at a pressure difference of 0.5 MPa for 10 min to obtain filter cake B1; 50 g of acetic acid was added to filter cake B1 and mixed thoroughly, and then pressure filtration was performed at a pressure difference of 0.2 MPa for 5 min to obtain filter cake B2; 25 g of acetic acid was added to filter cake B2, and then pressure filtration was performed at a pressure difference of 0.2 MPa for 5 min to obtain filter cake B3; 50 g of pure water was added to filter cake B3, and then pressure filtration was performed at a pressure difference of 0.2 MPa for 5 min to obtain filter cake B4; 25 g of pure water was added to filter cake B4, and then pressure filtration was performed at a pressure difference of 0.2 MPa for 5 min to obtain filter cake B5; filter cake B5 was placed in an oven at 120°C for 24 hours to dry to obtain filter cake B6.
[0094] Prepare a certain amount of crude TA slurry (based on 100 parts by weight, 2 parts of acetic acid, 4 parts of filter cake B6, and 94 parts of pure water), stir and mix thoroughly, and preheat to 280°C to make it a uniform solution;
[0095] 50.0g of pure water was added to a fixed bed hydrogenation reactor, and then 179.29g of a palladium-tin-carbon catalyst with a particle size of 5-8 mesh and a palladium content of 0.33wt% and a tin content of 0.15wt% was added, and then the temperature was raised to 280°C, and hydrogen was introduced, and the hydrogen partial pressure was controlled at 0.60MPa. The above-mentioned crude TA slurry was added to the fixed bed hydrogenation reactor at a rate of 7.41g / min to start the reaction. After the reaction was carried out for 5h, the hydrogenation purification material was collected, 2000g of the above-mentioned hydrogenation purification material was taken, and a positive pressure filtration device was used for solid-liquid separation to obtain a solid phase material (containing about 10wt% water, 80.0g hydrogenation purified PTA), which was then added to a high-temperature and high-pressure washing tank, and 160g of pure water was added. Stirring was started (200rpm), and the temperature was raised to 185°C after a sealed pressure test. The solid phase material was obtained after filtration and then dried to obtain PTA sample B7 for analysis. The analysis results are shown in Table 1.
[0096] 1015.00g of the above-mentioned oxidation raw material 2 and 8176.92g of the above-mentioned catalyst-containing solution 2 were pre-added to the oxidation reactor, the stirring paddle was turned on and its speed was set to 60rpm, and when the temperature was raised to 160°C, air was introduced into the oxidation reactor at a flow rate of 50.0L / min (standard state) and the air partial pressure was controlled at 0.5MPa. The back pressure valve behind the tail gas outlet was adjusted to control the pressure in the reactor to 4.0MPa, and the tail gas generated by the reaction was continuously discharged through the tail gas outlet. The reaction temperature was controlled at 190°C. After the reaction for 30 minutes, the oxidation raw material 2 and the catalyst-containing solution 2 were added to the bottom position of the oxidation reactor through the raw material inlet and the catalyst inlet at a rate of 10.15g / min and 81.77g / min, respectively. After the reaction for 30 minutes, 91.92g of crude 2,6-NDCA slurry was discharged from the outlet. / min rate of continuous discharge (crude 2,6-NDCA oxidation slurry), collecting the crude 2,6-NDCA oxidation slurry; based on 100g of the above crude 2,6-NDCA oxidation slurry, sequentially undergoing the following treatments: direct pressure filtration at a pressure difference of 0.5MPa for 10min to obtain filter cake C1; 50g of acetic acid was added to the filter cake C1 and fully mixed, followed by pressure filtration at a pressure difference of 0.2MPa for 5min to obtain filter cake C2; 25g of acetic acid was added to the filter cake C2 and then pressure filtration at a pressure difference of 0.2MPa for 5min to obtain filter cake C3; 50g of pure water was added to the filter cake C3 and then pressure filtration at a pressure difference of 0.2MPa for 5min to obtain filter cake C4; 25g of pure water was added to the filter cake C4 and then pressure filtration at a pressure difference of 0.2MPa for 5min to obtain filter cake C5; filter cake C5 was placed in an oven at 120°C for 24h to dry to obtain filter cake C6.
[0097] Prepare a certain amount of crude 2,6-NDCA slurry (based on 100 parts, 2 parts of acetic acid, 4 parts of filter cake C6, and 94 parts of pure water), stir and mix thoroughly, and preheat to 280°C to make it a uniform solution state;
[0098] 50.0g of pure water was added to a fixed bed hydrogenation reactor, and then 179.29g of a palladium-tin-carbon catalyst with a particle size of 5-8 mesh and a palladium content of 0.33wt% and a tin content of 0.15wt% was added, and then the temperature was raised to 280°C, and hydrogen was introduced, and the hydrogen partial pressure was controlled at 0.60MPa. The crude 2,6-NDCA slurry was added to the fixed bed hydrogenation reactor at a rate of 7.41g / min to start the reaction. After the reaction was carried out for 5h, the hydrogenation purification material was collected, 2000g of the above hydrogenation purification material was taken, and a positive pressure filtration device was used for solid-liquid separation to obtain a solid phase material (containing about 10wt% water, 80.0g hydrogenation purified 2,6-NDCA), and then added to a high temperature and high pressure washing tank, and then 160g of pure water was added, stirring was started (200rpm), and the temperature was raised to 185°C after the sealed pressure test, and the solid phase material was obtained after filtration and then dried to obtain 2,6-NDCA sample C7 for sample analysis. The analysis results are shown in Table 1.
[0099] According to the purity of sample B7 (PTA) and sample C7 (2,6-NDCA), the final preparation was sample D (i.e., PET_PEN copolyester monomer) at a weight ratio of 29.2:1 (since their corresponding purities are 98.83wt% and 98.14wt%, respectively, the target product yield can be regarded as ≈100%, so it can be converted into a weight ratio of 19:1 between the oxidized raw material PX and 2,6-DMN). The results are shown in Table 1.
[0100] Comparative Example 2
[0101] The method of comparative example 1 is followed, except that: a catalyst-containing solution 2 is prepared: based on a total of 100 g, 2.22 g of cobalt acetate tetrahydrate, 4.04 g of manganese acetate tetrahydrate, 3.64 g of potassium bromide, 4.50 g of potassium acetate, and 85.60 g of acetic acid. PTA and 2,6-NDCA samples L7 and M7 are obtained respectively.
[0102] After the samples were sent for analysis, according to the purity of sample L7 (PTA) and sample M7 (2,6-NDCA), the weight ratio was 29.20:1 (since their corresponding purities were 98.83wt% and 98.05wt% respectively, the target product yield can be regarded as ≈100%, so it can be converted into a weight ratio of 19:1 between the oxidized raw material PX and 2,6-DMN) to finally prepare sample N (i.e., PET_PEN copolyester monomer). The results are shown in Table 1.
[0103] According to the purity of sample L7 (PTA) and sample M7 (2,6-NDCA), the weight ratio of 11.27:1 (due to their corresponding purities of 98.83wt% and 98.05wt% respectively, the target product yield can be regarded as ≈100%, so it can be converted into a weight ratio of 7.33:1 between the oxidized raw material PX and 2,6-DMN) to finally prepare sample M (i.e., PET_PEN copolyester monomer). The results are shown in Table 1.
[0104] Table 1
[0105]
[0106]
[0107]
[0108] It can be seen from the results in Table 1 that the mixed oxidation reaction and hydrofining of terephthalic acid and 2,6-dialkylnaphthalene according to the present invention has a significant improvement effect compared with the oxidation reaction and hydrofining reaction of the two alone, and can improve the purity of terephthalic acid / 2,6-naphthalene dicarboxylic acid products and reduce the impurity content.
[0109] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing PET_PEN copolyester monomer, characterized in that: The preparation method comprises: in the presence of an oxidation catalyst and a first solvent, a raw material containing 2,6-dialkylnaphthalene and p-xylene is contacted with an oxygen-containing gas to carry out an oxidation reaction, and then is refined.
2. The preparation method according to claim 1, wherein In the raw material, the weight ratio of 2,6-dialkylnaphthalene to p-xylene is 0.020-0.111:1, preferably 0.042-0.064:1; and / or The weight ratio of the oxidation catalyst to the first solvent is 0.01-0.035:1; and / or The weight ratio of the first solvent to the raw material is 1.5-9:1, preferably 4-9:
1.
3. The preparation method according to claim 1 or 2, wherein The 2,6-dialkylnaphthalene is selected from at least one of 2,6-dimethylnaphthalene, 2,6-diisopropylnaphthalene and 2,6-diethylnaphthalene, preferably 2,6-diisopropylnaphthalene; and / or The first solvent comprises a carboxylic acid substance and optionally water, preferably the water content in the first solvent is ≤8wt%; preferably the carboxylic acid substance is selected from saturated fatty acids; more preferably, the carboxylic acid substance is selected from C2 to C6 saturated fatty acids; further preferably, the carboxylic acid substance is selected from acetic acid; and / or The oxygen-containing gas is oxygen and / or air.
4. The preparation method according to any one of claims 1 to 3, wherein The active components of the oxidation catalyst include manganese, bromine, cobalt and optionally potassium; Preferably, the manganese element, the cobalt element and the potassium element are each derived from a salt of the corresponding element; and / or The bromine element is derived from bromide; More preferably, the molar ratio of the manganese salt to the cobalt salt is 1.5-4.5:1, preferably 2.0-3.5:1; and / or The molar ratio of the sum of the cobalt salt and the manganese salt to the bromide is 0.7-1.5:1, preferably 0.85-1.25:1; and / or The weight ratio of potassium salt to oxidation catalyst is 0.1-0.85:1, preferably 0.3-0.65:
1.
5. The preparation method according to any one of claims 1 to 4, wherein: The oxidation reaction is a continuous oxidation reaction; and / or The molar ratio of oxygen in the oxygen-containing gas to the raw material is 2.5-9:1, preferably 2.8-4.0:1; Preferably, based on the advance feeding of 1000 g of the raw material and the continuous feeding of the raw material at 10 g / min, the flow rate of the oxygen-containing gas under standard state is 20.0-88.0 L / min, preferably 20.0-60.0 L / min; and / or the oxygen content in the oxygen-containing gas is 18.0-25.0 vol%; and / or the partial pressure of the oxygen-containing gas is 0.3-0.8 MPa; and / or The conditions of the oxidation reaction include: The reaction temperature is 160-220°C, preferably 170-200°C; and / or The reaction pressure is 1.8-4.0 MPa, preferably 2.0-3.5 MPa; and / or The raw material is a liquid raw material, and the residence time of the liquid raw material in the oxidation reaction is 0.5-2.0h, preferably 0.9-1.8h.
6. The preparation method according to any one of claims 1 to 5, wherein: The refining process comprises: hydrogen gas is contacted with the slurry containing crude 2,6-naphthalene dicarboxylic acid / terephthalic acid obtained by oxidation reaction in the presence of a hydrogenation catalyst and a second solvent for hydrogenation refining; Preferably, the material obtained by the oxidation reaction is subjected to solid-liquid separation, optional washing separation, water solvent replacement, and drying to obtain crude 2,6-naphthalene dicarboxylic acid / terephthalic acid.
7. The preparation method according to claim 6, wherein: The hydrogenation catalyst is selected from supported noble metal catalysts; Preferably, the particle size of the supported noble metal catalyst is 5-8 mesh; and / or The content of the noble metal in the supported noble metal catalyst is 0.1-0.8 wt%, preferably 0.35-0.65 wt%; and / or In the supported precious metal catalyst, the precious metal is selected from one or more of palladium, ruthenium and tin, preferably palladium and tin, and more preferably the weight ratio of palladium to tin is 1-9:
1.
8. The preparation method according to claim 6 or 7, wherein: The solvent in the slurry includes a mixture of carboxylic acid substances and water; Preferably, the weight ratio of the carboxylic acid substance to water is 0.01-0.1:1, preferably 0.015-0.08:1; and / or The carboxylic acid substance is selected from one or more of formic acid, acetic acid and propionic acid, preferably acetic acid.
9. The preparation method according to any one of claims 6 to 8, wherein: In the slurry, the weight ratio of the solvent to the crude 2,6-naphthalene dicarboxylic acid / terephthalic acid is 15-40:1, preferably 18-30:1; and / or The second solvent comprises water; and / or The mass ratio of the second solvent to the hydrogenation catalyst is 0.1-1:1, preferably 0.2-0.5:
1.
10. The preparation method according to any one of claims 6 to 9, wherein: The conditions of the hydrofining include: Relative to the hydrogenation catalyst, the liquid hourly weight space velocity LHSV of the slurry is n 0.25-10h -1 , preferably 0.5-8h -1 ; and / or The reaction temperature is 250-310°C, preferably 270-290°C; and / or The hydrogen partial pressure is 0.05-3.0 MPa, preferably 0.5-1.5 MPa; and / or The refining process also includes solid-liquid separation, washing, and drying of solid phase substances after refining.